Inhibition of Glycogen Synthase Kinase 3β Ameliorates D-GalN/LPS-Induced Liver Injury by Reducing Endoplasmic Reticulum Stress-Triggered Apoptosis - Chen, Liyan (Public Library of Science, 2012)
BACKGROUND: Glycogen synthase kinase 3β(GSK3β) is a ubiquitous serine-threonine protein kinase that participates in numerous cellular processes and disease pathophysiology. We aimed to determine therapeutic potential of GSK3β inhibition and its mechanism in a well-characterized model of lipopolysaccharide (LPS)-induced model of acute liver failure (ALF). METHODOLOGY: In a murine ALF model induced by D-GalN(700 mg/kg)/LPS(10 µg/kg), we analyzed GSK3β mechanisms using a specific chemical inhibitor, SB216763, and detected the role of endoplasmic reticulum stress (ERS). Mice were administered SB216763 at 2 h before or after D-GalN/LPS injection, respectively, and then sacrificed 6 h after D-GalN/LPS treatment to evaluate its prophylactic and therapeutic function. The lethality rate, liver damage, ERS, cytokine expression, MAP kinase, hepatocyte apoptosis and expression of TLR 4 were evaluated, respectively. Whether the inhibition of GSK3β activation protected hepatocyte from ERS-induced apoptosis was investigated in vitro. PRINCIPAL FINDINGS: GSK3β became quickly activated (dephosphorylated) upon D-GalN/LPS exposure. Administration of SB216763 not only ameliorated liver injury, as evidenced by reduced transaminase levels, and well-preserved liver architecture, but also decreased lethality. Moreover, GSK3β inhibition resulted in down-regulation of pro-apoptotic proteins C/EBP–homologous protein(CHOP) and caspase-12, which are related to ERS. To further demonstrate the role of ERS, we found that GSK3β inhibition protected hepatocyte from ERS-induced cell death. GSK3β inhibition down-regulated the MAPK pathways, reduced expression of inflammatory cytokines and decreased expression of TLR4. CONCLUSIONS: Our findings demonstrate the key function of GSK3β signaling in the pathophysiology of ALF, especially in regulating the ERS, and provide a rationale for targeting GSK3β as a potential therapeutic strategy to ameliorate ALF.